Pola Interaksi Anak dengan Ayah Tiri dalam Keluarga Remarriage - Indah Sari Rahmaini (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2021)
Children are an asset of the nation that must be guarded and protected. But the child in the family remarriage in particular relationship with the father is less fulfilled its rights that can be seen from the interaction that occurred. The study aimed to describe the pattern of interaction of children with stepfathers in the family remarriage. This study was conducted with qualitative approach and informants were chosen by purposive technique as well as in data collection using observation technique and in-depth interview. The theory used is the symbolic interactionism of Herbert Blumer. The results of this study was the social setting of the interaction of children with stepfathers was the dinner together, the accompaniment of children learning, watching TV together, the transfer of children to school, recreation, and visiting the stepfather's family. The social context of child interaction with stepfathers was the interaction as a means of communication, interaction as the purpose of communication, and the involvement of the mother in the interaction. For interaction as a means of communication was giving advice to children and giving rewards to children. The interaction as the purpose of communication was farewell and shake before traveling and direct the orientation of the child forward.